Recent Advances in Anti-Epileptic Drugs - KHAN, S.A.; LAMBA, H.S.; RATHOUR, ARVIND; BUDHWAAR, VIKAS; PAHWA, RAKESH; MANJUSHA (Asian Journal of Chemistry, 2010)
Epilepsies are a group of disorders of the CNS characterized by paroxysmal cerebral dysrhythmia, manifesting as brief episodes (seizures) of loss or disturbance of consciousness, with or without characteristic body movements (convulsions), sensory or psychiatric phenomena. Epilepsy has a focal origin in the brain, manifestations depend on the site of the focus, regions into which the discharges spread. Some newer anti-epileptic drughs have recently been developed. They have some advantages over the older drugs. These newer drugs may control seizures more effectively. They are effective in complex partial and secondary generalized seizures. These are felbamate, vigabatrin, gabapetin, clobazam, lamotrigine, oxcarbazepine, tiagabine, topiramate, fosphenytoin and zonisamide.